The Gooey Behaviour Among Millennial Learners in a Malaysian Institute of Higher Learning - Cheng, Sheila; Siow, Heng Loke (Open University of Hong Kong, 2016)
A report from Informate Mobile Intelligence in 2015 indicated that people in the US checked their social media which accounted a whopping 17 times a day. But in this context, Americans are not alone. Smartphone users in Malaysia, Thailand, Argentina, Mexico, South Africa and Qatar checked these networking applications at least 40 times a day. Davis (2015) reported that people spent an average of 8 hours 41 minutes on media devices. We term the act of these netizens being incessantly glued to the smartphones as a gooey behaviour. In Malaysia, this gooey behaviour among the millennial learners has resulted in two significant impacts, especially on the roles of the classroom instructor. On the positive side, it helped to authenticate the data of instructors while the negative side it was to be distracted to other non-related activities. Both behaviours have posed challenges to the ‘traditional’ pedagogical mode. This paper presents a sample of 42 students of age 20-25 who were undergraduates and were studying in a Malaysian HEI. A mixed-research methodology was employed in which included a questionnaire survey and face-to-face interviews. The millennial learners indicated their views on “an interesting lecture” to be a lecture that should be fun, useful and meaningful, able to makes students’ curious and attract their attention. The results of this paper call for a disruptive innovation of teaching and learning, and transformation of pedagogy. It also provides insights to instructors who are designers of their lessons on how to orchestrate a lesson so as to engage these gooey netizens.